The Impact of Rotating Night Shift Work and Daytime Recharge on Cognitive Performance Among Retired Nurses - Gan, Jinghuan; Wang, Xiao-Dan; Shi, Zhihong; Yuan, Junliang; Zhang, Meiyun; Liu, Shuai; Wang, Fei; You, Yong; Jia, Peifei; Feng, Lisha; Xu, Junying; Zhang, Jinhong; et al. (Frontiers in Aging Neuroscience, 2022)
Introduction The exact relationship between long-term shift work (SW) and cognitive impairment (CI) has been poorly understood. The effects of the long-term rotating night SW (RNSW) combining daytime recharge (DTR) on cognitive function were investigated. Methods A total 920 retired nurses and 656 retired female teachers aged ≥50 years were analyzed. Participants who worked at least once per week for 8 hat night for more than 1 year were defined as the SW group, and those without a regular nighttime shift were defined as the control group. The associations among duration, frequency, and DTR of RNSW, and neuropsychological assessments were ascertained by regression models. Results Participants with RNSW had a significantly higher proportion of mild CI (MCI), both amnestic MCI (aMCI) (14.4% in 11–20 years, p < 0.05, and 17.8% in > 20 years, p < 0.001) and non-amnestic MCI (naMCI) (8.1% in 11–20 years, p < 0.05), as well as dementia (1.5% in 1–10 years, and 11.7% in > 20 years, p < 0.05) compared to controls (8.4% with aMCI, 4.4% with naMCI, and 7.0% with dementia, respectively). There were significant negative relationships between general times of night SW and scores of Mini-Mental State Examination (MMSE) (R squared = 0.01, p = 0.0014) and Montreal Cognitive Assessment (MoCA) (R squared = 0.01, p = 0.0054). Participants with ≥1 h of DTR and ≥ 11 years of RNSW were about 2-fold more likely to experience MCI compared with the subjects in the control group, especially with 3–5 h (odds ratio [OR]: 2.35; 95% confidence interval: 1.49–3.68, p < 0.001). Conclusion The long-term RNSW was associated with a higher risk of CI, especially aMCI and dementia, and the problem cannot be improved by DTR.